2017
DOI: 10.7554/elife.27293
|View full text |Cite
|
Sign up to set email alerts
|

Akt regulation of glycolysis mediates bioenergetic stability in epithelial cells

Abstract: Cells use multiple feedback controls to regulate metabolism in response to nutrient and signaling inputs. However, feedback creates the potential for unstable network responses. We examined how concentrations of key metabolites and signaling pathways interact to maintain homeostasis in proliferating human cells, using fluorescent reporters for AMPK activity, Akt activity, and cytosolic NADH/NAD + redox. Across various conditions, including glycolytic or mitochondrial inhibition or cell proliferation, we observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…Activation of AMPK and its downstream effectors may be beneficial for treating diabetes, cancer, and other diseases, and there have been a number of efforts to develop pharmacological AMPK activators (Cokorinos et al, 2017;Myers et al, 2017). In particular, biguanides are an important class of diabetes drug that act in part as ETC inhibitors, and which induce cyclic AMPK activation similar to that shown here (Hung et al, 2017a). Understanding the kinetics of AMPK in response to ETCi challenges, and the factors that underlie the heterogeneous ETCi response, will be important in optimizing AMPK activation strategies for beneficial cellular effects.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Activation of AMPK and its downstream effectors may be beneficial for treating diabetes, cancer, and other diseases, and there have been a number of efforts to develop pharmacological AMPK activators (Cokorinos et al, 2017;Myers et al, 2017). In particular, biguanides are an important class of diabetes drug that act in part as ETC inhibitors, and which induce cyclic AMPK activation similar to that shown here (Hung et al, 2017a). Understanding the kinetics of AMPK in response to ETCi challenges, and the factors that underlie the heterogeneous ETCi response, will be important in optimizing AMPK activation strategies for beneficial cellular effects.…”
Section: Discussionmentioning
confidence: 54%
“…However, this variation could also arise from other sources, including non-linearity or non-specificity in the reporter readout. We investigated these alternatives using the non-tumor epithelial cell line MCF10A, a system that responds with metabolic changes to physiological signals including insulin, growth factors, and attachment (Grassian et al, 2011;Hung et al, 2017a;Schafer et al, 2009). To quantitatively relate AMPKAR2 reporter signals to cellular AMPK activity, we calibrated the FRET ratio measured by microscopy to AMPKAR2 phosphorylation status using Phos-tag electrophoresis ( Figure S1A-B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a study has shown that TGF-b1 could also activate the phosphatidylinositol 3 kinase-protein kinase B (PI3K-Akt) signaling pathway 8 . The PI3K-Akt pathway is involved in many cellular processes, including proliferation, differentiation, apoptosis, tumor growth and cell cycle progression [9][10][11] . Therefore, it is important to know whether there is a relationship among costimulation of TGF-b1 and high glucose, podocyte apoptosis and the PI3K-Akt pathway, and the details.…”
Section: Introductionmentioning
confidence: 99%